THE INFLUENCE OF CONSUMER CHARACTERISTICS AND SITUATIONAL FACTORS ON ONLINE IMPULSIVE BUYING OF FASHION PRODUCTS - Intan Destyanawati; Soepatini (IAIN Surakarta, 2023)
This study aims to analyze the influence of consumer characteristics (impulse buying tendencies, shopping enjoyment tendencies, and consumer moods) and situational factors (individual situation, website quality, motivational activity by retailers, and product attributes) on online impulsive purchases of fashion products in the past pandemic. The population in this study were people who live in Surakarta and Solo Residency with a sample of 100 respondents. The data collection method used a questionnaire, and was processed using the Partial Last Square (PLS). Data analysis used in this study included instrument tests, classic assumption tests consisting of multicollinearity tests, Goodness of Fit (GoF) tests and partial tests (t-test). The results of the study show that first, there are four accepted hypotheses where the factors that influence online impulsive purchases of fashion products are shopping enjoyment tendencies, shopping enjoyment tendencies, consumer moods, and product attributes. Second, other factors such as individual situation, website quality, and motivational activity by retailers are not the determining factors.